Establishing the national boundaries - Logan, Daniel Andrew (My University, 1905)
Introduction: The boundary line of a country is a matter of small significance when it happens to be land bordering on the water, but on such places on the land it is often the cause of constant irritation and disputes between the two adjacent countries. The boundary line decides whether or not a person must obey one or another code of laws and fight for one or another country. It is a very difficult matter to run a boundary line over a country or continent. The first difficulty lies in the fact that the people on each side of the boundary line are about the same. They live the same, have the same habits and customs, yet they are governed by a different set of officials and must obey a different code of laws. Another difficulty lies in the fact that the line is more or less imaginary and inaccurate, due to the inaccuracy of our surveying instruments and to our natural aptitude of being greedy. Oceans, lakes and rivers form the best boundary lines. Other land marks such as chain of highlands or a watershed also form natural boundaries.
Citation: Logan, Daniel Andrew. Establishing the national boundaries. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Boundary; Boundaries at Dawn of Existance; Lousiana Purchase; Theses